What is the effect of systemic anticancer treatment on cognitive function? - (:unkn) unknown (ELSEVIER SCIENCE INC, 2004)
Treatment regimens for solid tumours have been extensively investigated for their physical toxic effects, but far less is known about the potential impairment of cognitive function by anticancer treatment regimens. Here, we review published studies that examined cognitive function in adult patients receiving systemic therapy for solid tumours. Our review suggests that patients can experience cognitive changes related to their treatment. However, several studies had methodological limitations, such as use of a limited sample size, lack of baseline assessment, and lack of control for potential confounding factors. Better designed clinical trials are required so that the difficulties patients face in terms of reduced cognitive function as a result of anticancer treatment can be fully elucidated. These trials should have sufficient statistical power and, importantly, should also be prospective.
Keywords: CELL LUNG-CANCER; HIGH-DOSE CHEMOTHERAPY; CENTRAL-NERVOUS-SYSTEM; LONG-TERM SURVIVORS; PROPHYLACTIC CRANIAL IRRADIATION; CONTROLLED CLINICAL-TRIAL; BREAST-CANCER; ADJUVANT CHEMOTHERAPY; POSTMENOPAUSAL WOMEN; RANDOMIZED TRIAL